Constitutional Guarantees and Justice in Indonesia’s Poverty Alleviation Programs (2014–2024) - Abqa, Muhammad Ardhi Razaq; Saraswati, Retno; Sa'adah, Nabitatus; Yusliwidaka, Arnanda (Universitas Islam Negeri Raden Intan Lampung, 2025)
Poverty alleviation is a central issue in sustainable development and is the constitutional mandate of the Indonesian state. This article analyses the role of constitutional guarantees, the positive impact of poverty alleviation programs 2014-2024, and policy implementation challenges. This study uses a qualitative approach with a normative and empirical legal research design. Normative legal studies focus on the legal basis of policies, while empirical studies examine policy implementation in the field. This research uses the theory of justice. The results show; First, Indonesia's constitutional guarantee is a strong legal basis for poverty alleviation. Articles in the 1945 Constitution provide a solid foundation for realizing justice. Second, the KIS, KIP, and PKH programs improve the welfare of low-income people. Third, challenges in policy implementation include access gaps between regions, budget instability, limited supervision, weak institutional capacity, and uneven digital infrastructure. This research concludes that the KIS, KIP, and PKH programmes reflect the mandate of social justice in the 1945 Constitution and are proven to improve the welfare of the poor. However, structural and implementation barriers require strengthening regulations, coordination, and digital infrastructure to realize equitable and sustainable poverty alleviation.